Locative prepositions “at, in, on” and translation to Vietnamese representational meaning - Tuyet Hanh, Nguyen Thi (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2022)
Starting with the role of the reference frame under the influence of the perspective culture of the British and Vietnamese used as a cognitive premise of translation, the article presents the rationale for the procurement process on reasons, similarities, and differences in the representational meaning. The representational meaning of differences between the English locative preposition “at, in, on” and the corresponding linguistic units of Vietnamese through a particular communication context. According to the research results, when the reference object (DTQC) of the English locative position in the reference system is assimilated with the Vietnamese speaker [similar to the reference frame of the reference system], the translation semantics of the locative prepositions which is ​​